Molecular epidemiology of camel contagious ecthyma in Arero district, Ethiopia - Diba, Bareda (2023)
Questionnaire survey results Herd profile of the respondents is described in Table 1. Herd size was used to evaluate the relative contribution of camels to pastoralists and herding years was used to estimate their practices in camel husbandry. Out of the total interviewed respondents (n = 129), the majority (48%) were in age range of 42–61 years. Average herd size of the respondents was 13camels, and more than 40% (46.3%) had over ten years herding experiences.